Investigation on the Crack Initiation of V-Shaped Notch Tip in Precision Cropping - Lijun Zhang; Shengdun Zhao; Zhenwei Wang (Advances in Materials Science and Engineering)
The crack initiation of V-shaped notch tip has a very important influence on the cross-section quality and the cropping time for every segment of metal bar in course of low stress precision cropping. By the finite element method, the influence of machining precision of V-shaped notch bottom corner on the crack initiation location is analyzed and it is pointed out that the crack initiation point locates in the place at the maximal equivalent stress change rate on V-shaped notch surface. The judgment criterion of the crack initiation direction is presented and the corresponding crack initiation angle can be calculated by means of the displacement extrapolation method. The factual crack initiation angle of the metal bar has been measured by using the microscopic measurement system. The formula of the crack initiation life of V-shaped notch tip is built, which mainly includes the stress concentration factor of V-shaped notch, the tensile properties of metal material, and the cyclic loading conditions. The experimental results show that the obtained theoretical analyses about the crack initiation location, the crack initiation direction, and the crack initiation time in this paper are correct. It is also shown that the crack initiation time accounts for about 80% of the cropping time for every segment of the metal bar.